The teacher-student relationship as a predictive variable of school engagement: The mediating role of subjective well-being in a structural equation model with indigenous students aged 10 to 14 years old - Joaquín Brieba-Fuenzalida (Revista Española de Pedagogía, 2025)
The teacher-student relationship is a key factor in students’ academic performance, school engagement, and subjective well-being. However, little is known about how this relationship influences these variables among Indigenous students, particularly Mapuche students in Chile. This study evaluates a predictive model of the teacher-student relationship on school engagement and the role of subjective well-being in this relationship in Mapuche students aged 10 to 14. A cross-sectional design was used, with a sample of 300 students aged 10 to 14. Structural equation modeling (SEM) was employed to analyze the relationships among the teacher-student relationship, school engagement, and subjective well-being. Results revealed a moderate significant direct effect of the teacher-student relationship on school engagement (β = .359, p <.001) and subjective well-being (β = .398, p <.001). Moreover, subjective well-being had a significant positive direct effect on school engagement (β = .402, p <.001), suggesting that students with higher levels of well-being exhibit greater school engagement. An indirect effect was also observed between the teacher-student relationship and school engagement, mediated by subjective well-being (β =.160, p <.001). These findings support the hypothesis that subjective well-being strengthens the impact of teacher-student relationships on school engagement. Although the effect size was small, the statistical power of the findings highlights their relevance. Limitations such as the cross-sectional design -restricting causal inferences- and suboptimal reliability indices in the behavioral dimension of school engagement must be considered in future replications. These findings contribute valuable evidence for the development of culturally relevant educational interventions aimed at improving Indigenous students’ engagement and enhancing well-being of Indigenous students. They also underscore the urgency of formulating public policies that focus not only on academic achievement but also on the holistic development of students.